Extraction and purification of phytosterols mixture from Palm Fatty Acid Distillate (PFAD) using multistage extraction processes - Jalani, Nor Faizah; Abdul Wahab, Noorshamsiana; Wan Hassan, Wan Hasamudin; HASSAN, KAMARUDIN; Zainal, Nahrul Hayawin; Ibrahim, Mohamad Faizal (Malaysian Palm Oil Board, 2021)
Phytosterols are among the bioactive compounds naturally present in vegetable oils and their by-products or derivatives. A phytosterol resource (PSR), solid by-product from the extraction of vitamin E in palm fatty acid distillate (PFAD), contains 2%-4% (w/w) total sterols. Therefore, the extraction of phytosterols from the PSR in a mini-pilot scale involving multistage extraction processes was developed to recover the valuable minor component. The multistage extraction and purification processes comprised of solid-liquid extraction (SLE) with hexane at 35°C in 1 hr, saponification reaction at the reflux temperature of 80°C for 1 hr, liquidliquid extraction (LLE) with hexane and water, and crystallisation and vacuum filtration at -5°C for 20 hr. On average, gas chromatographic (GC) analysis showed the phytosterols recovered from the extraction and purification process had more than 80% purity. The recovery of total sterols from the PSR was 84% composed of β-sitosterol (21%-22%), campesterol (13%-20%) and stigmasterol (59%-64%). This extraction process is technically feasible to extract and produce crude phytosterols from a PFAD by-product.